The Presence of Helicobacter pylori in cases of Chronic Tonsillitis in Medan - Harahap, Rini Syahrani; Delyuzar; Jessy Chrestella (Sumatera Medical Journal, 2020)
Background: Helicobacter pylori is a well known pathogen which is recognized as the most frequent infection of individuals. Helicobacter pylori plays important role in the etiology og gastritis, gastric and duodenal ulcers. We investigated the presence of Helicobacter pylori as an extragastric reservoir in the tonsilectomy specimens. Aim: To determine the presence of Helicobacter pylori in cases of chronic tonsillitis in tonsilectomy specimens. Methods: This is a descriptive study with cross sectional which the sample will be obtained using consecutive sampling method. We collect 43 cases with chronic tonsilitis were examined in tonsillectomy specimens for which available tissue for routin staining could be retrieved were histopathology chronic tonsillitis. The colonization of the helicobacter pylori have been evaluated with hematoxylin & Eosin and Giemsa stains under the light microscope. Results: With H&E staining, Helicobacter pylori has been detected in 23 cases (53,48%) of the tonsil-lectomy specimens in total. No colonization has been observed in the remaining 20 cases (46,51%). With giemsa staining Helicobacter pylori has been detected in 29 cases (67,74%) of the tonsillectomy specimens in total. No colonization has been observed in the remaining 14 cases (32,55%). Keywords: Helicobacter pylori, Chronic Tonsillitis, H&E, Giemsa.